The New World Order in the Twenty-First Century - Motaharnia, Mehdi; Salehi, Ensiyeh (Journal of History Culture and Art Research, 2017)
Thinking about the future is not a new issue. This concept is a universal phenomenon that can be probed its root in pre-human history. In all known human societies, people have ideas about time and future. The existence of such notions in all human societies is an undeniable reality. The risks of failure due to lack of preparation for the future, after the frenzied competition in global stock markets also showed face. In such an atmosphere, more than ever required that the futurist thinkers put the effort necessary to develop scenarios to get out of this crippling over the question of whether the future will be? The present paper is discussed existing scenarios on the future of the international system to express this scenario that the future of the international system will be a flexible bipolar system that capitalism rallying against each other where foundation of knowledge in both the West with East, China and America’s flagship. This order within itself will be facing with the chaos caused by the fatness of nation’s wisdom against state power. This feature would cause a problematic international order in the near future other than any times.